Extraction processes reduce polyphosphate ion migration, dispersion and diffusion as detected with gel electrophoresis and 31P DOSY NMR. Issue 20 (4th September 2022) - Manoukian, Lori; Correa, José A.; Stein, Robin S.; Frigon, Dominic; Omelon, Sidney
Abstract: Inorganic polyphosphates (polyPs) have been identified in eukaryotic and prokaryotic cells alike. Various extraction methods have been optimized as a necessary step before identification and measurement of these polymers. Three commercially available sodium polyP glasses were either dissolved or dissolved and extracted by two commonly used polyP extraction techniques – perchloric acid or buffered phenol–chloroform. The products were separated by polyacrylamide gel electrophoresis (PAGE), stained with toluidine blue O, and the migration results quantitatively compared. Both extraction processes reduced the relative migration distances of the peak and leading edges, and the stained band lengths, suggesting reduced polyP migration and dispersion. 31 P diffusion‐ordered spectroscopy nuclear magnetic resonance confirmed that polyP extraction by perchloric acid or phenol–chloroform processes reduced polyP diffusion coefficients and suggested hydrolytic degradation with stronger end‐chain signals. Reduced polyP diffusivity after extraction makes possible an overestimation of synthetic polyP chain length assignment when compared to unextracted polyP ladders with PAGE. The mechanism(s) for reduced synthetic polyP diffusion after extraction and intracellular chemical environment effects on migration are not known.